DIFFERENTIAL SUSCEPTIBILITY OF Popillia cupricollis (COLEOPTERA: SCARABAEIDAE: RUTELINAE) TO DIFFERENT GROUPS OF INSECTICIDES (Applied Biological Research, 2023)
Scarabaeidae is the 2nd largest family within the Order Coleoptera and worldwide has about 30,000  species with 13 subfamilies, of which Melolonthinae and Rutelinae are the largest cosmopolitan  subfamilies (Khanal et al., 2012). The family Scarabaeidae is represented by 2,500 species in India  (Pathania et al., 2015). Most species in sub-family Melolonthinae and Rutelinae are destructive and  notorious insect pests. Both adult and larva are pestiferous and cause severe damage to the field-,  fruit- and tree-crops, and grasslands. In India, larvae of the scarab beetles have been identified as  one of the five national pests (Sharma, 2002). The scarab larvae cause an estimated reduction of 40- 80% in crop yield (Gite et al., 2015). In India, the North-Western Himalayan region comprising of the states of Uttarakhand, Himachal Pradesh and Jammu & Kashmir has been identified as hot spot for white grub diversity (Subbanna et al., 2020). In this region, maximum cropped area is under  well-drained sandy soil along the hill slopes which favours the growth and development of white  grubs. The varied altitude, steepness, microclimate, and availability of food for both adults and  larvae in Uttarakhand make it favourable for scarab diversity. Numerous practices such as physical,  behavioural, biological, chemical, cultural, mechanical, and integrated methods have been adopted  for white grub management (Paschapur et al., 2017). Of these, chemical control is considered as the  first line defense against these species under pest outbreak conditions, as they emerge in large  numbers and get concentrated on host trees for feeding and mating. Therefore, the selection of most  efficient insecticide for timely and effective management is essential to minimize the number of  adults and grub populations under field conditions. The shiny chafer beetle, Popillia cupricollis, is  diurnal in nature and no synthetic attractant is available or reported to lure and trap this beetle. It is  difficult to manage it by using cultural (light trap) and behavioural (pheromone trap) tactics. The  chemical control is the only available strategy used to manage P. cupricollis population in field  during pest outbreak. But, species-specific information regarding the insecticidal management of P.  cupricollis is not available. So, the present study was aimed to generate information on the in vitro  susceptibility of P. cupricollis to 21 insecticides belonging to different chemical groups.